A color of his own - Lionni, Leo, 1910-1999 (New York : Scholastic, 2004)
A little chameleon is distressed that he doesn't have his own color like other animals.
British ed. published in 1975 under title: A colour of his own.
AD640L
Lexile
Accelerated Reader
Keywords: Chameleons -- Juvenile fiction; Color -- Juvenile fiction